An econometric model of production with endogenous improvement in energy efficiency 1970 - 1995 - Klaus Conrad (Fondazione Eni Enrico Mattei (FEEM), 1998)
The purpose of this paper is to introduce a modification of a standard four input production process where energy is used in an inefficient way due to partly unnecessary waste of energy. In this production process, R&D investment is an additional input in order to improve energy efficiency. It closes the gap between energy purchased and energy used effectively. The more is invested, the less is the waste of energy. With the cost and benefit of R&D investment incorporated in our model of the firm, we analyze the impact of an energy tax on R&D effort, on output and on the waste of energy. The model is implemented empirically by choosing a translog cost function and a set of first-order conditions, using data for the German chemical industry, 1970-1995. In a simulation study based on higher energy prices we found outsourcing as the consequent reaction of the firm - more material is used and less of energy, labor, and capital, given the unchanged output level. There is no indication of a double dividend in terms of environmental improvement as well as higher demand for labor on the industry level calling for a computable general equilibrium approach in order to answer this open question.
Keywords: C51; D21; O31; Q41; Q48; 330; Production process; Energy demand; Energy saving technical change; Process R&D expenditures; Energy tax; Ökonometrisches Makromodell; Energieeinsparung; Energiekonsum; Energiesteuer; Forschungskosten; Technische Effizienz; Chemieindustrie; Theorie; Deutschland